The diamond of Darkhold [compact disc, unabridged] - DuPrau, Jeanne (DuPrau, Jeanne. Ember, 2008)
In the year 241, twelve-year-old Lina trades jobs on Assignment Day to be a Messenger to run to new places in her decaying but beloved city, perhaps even to glimpse Unknown Regions.